Data for metabolomics and transcriptomics resources for the identification of candidate genes in the biosynthesis of specialized metabolites in Populus tremula (L). - M. Rydman, Sara; Robinson, Kathryn; Lihavainen, Jenna; Albrectsen, Benedicte R.; Jansson, Stefan; Street, Nathaniel (Umeå University, 2025)
Despite their importance, the pathways and enzymes associated with the biosynthesis of many specialized metabolites are yet to be characterized. The integration of multi-omics data represents a powerful approach to link genes encoding enzymes and their regulatory factors to metabolite biosynthesis. However, suitable multi-omics data resources for this approach are scarce. Here we present a data resource comprising Liquid Chromatography Mass Spectrometry (LC-MS) and mRNA-Sequencing data from European aspen (Populus tremula L.) including tissues sampled from different organs, and genotypes that produce contrasting sets of salicinoid phenolic glucosides (SPGs), that are specialized metabolites characteristic for Salicaceae.
Keywords: Plant biochemistry; Biological network analysis; Genomics and transcriptomics; Gene expression (incl. microarray and other genome-wide approaches); Medical and Health Sciences; Medicin och hälsovetenskap; Genetics and Genomics; Genetik och genomik